Pengaruh Kepercayaan dan Kemudahan terhadap Keputusan Pembelian Menggunakan Pinjaman Online Shopee PayLater - Fanny Anggraeny Putri; Sri Setyo Iriani (Jurnal Ilmu Manajemen, 2020)
This financial technology innovation continues to develop along with changes in people's lifestyles. Financial services that provide online loan facilities are currently trending as a means of payment for several large e-commerce in Indonesia. Shopee is e-commerce that has a PayLater facility as an alternative method of shopping transactions that provides loan funds under the name Shopee PayLater. The use of Shopee PayLater makes it easy for consumers to shop online through the Shopee marketplace even though they don't have enough funds to shop. This research is a quantitative study with a conclusive research design to determine the effect of trust and ease on purchasing decisions using online loans. Sampling technique on this research used judgmental sampling and snowball sampling with a sample size of 110 respondents that Shopee users. Which are Shopee users have once made transactions using ShopeePayLater. The results of this study indicate there is a significant positive influence between trust and ease of purchasing decisions using online loans. Based on the result, it is recommended that Shopee PayLater make pay attention and make sure that this application has guaranteed security, so it can build a good image to increase the trust and have an impact to purchase decisions towards online loans Shopee PayLater.